A Corpus-based Proposal for Teaching a Translational Habitus: Initial dialogues with Bourdieu’s sociological approaches - Serpa, Talita [UNESP]; Pinto, paula Tavares [UNESP]; De Camargo, Diva Cardoso [UNESP] (Malaga University, 2021)
There is a growing body of literature that recognises the importance of Social Sciences in Translation Studies, such as the discussions surrounding the translational habitus, developed by Simeoni, Wolf and Inghilleri. In our research, we associate these ideas to corpus methodologies to analyse terminological usages as part of a professional behaviour. We hypothesise that when translation students observe the most frequent terms extracted from a parallel corpus as well as their keyness and contexts prior to starting their translation, they replicate the same translational strategies in their texts, which can indicate the acquisition of competencies related to a particular habitus.
Una propuesta basada en corpus para enseñar un habitus de la traducción: diálogos iniciales con los enfoques sociológicos de Bourdieu
Keywords: Competencies; Corpus-based translation pedagogy; Teaching theories; Terminological usage; Translational habitus